Teacher's Perception of Environment Project-Based Collaborative Learning as Strengthening Implementation Curriculum of Merdeka - Utami, Dr. Wiwik Sri; Widodo, Dr. Bambang Sigit; Purnomo, Dr. Nugroho Hari; Zain, Ita Mardiani; Sutedjo, Agus; Prastiyono, Dr. Hendri; Prasad, Dr. Ravinesh Rohit (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2023)
Collaborative learning based on the environment project as a differentiating model from the implementation of the curriculum of Merdeka. This study aims to obtain teacher perceptions before and after workshops on collaborative learning based on the environment project as a practice of implementing an curriculum of Merdeka in schools. Teacher perceptions are very important in increasing competency in facilitating differentiated learning of their students as 21st-century learners. This study uses an exploratory study through a qualitative approach. This research involved 19 teachers of social and exact sciences at SMAN 3 Sampang. The teachers cover the fields of Geography, Economics, Sociology, History, Mathematics, Biology, and Chemistry. Teachers were as key informant. Data were collected from October 2022 using instruments developed. The data consisted of 17 questions about project-based collaborative learning as a strengthening implementation curriculum of Merdeka. Data collection was carried out through deep interviews, observation, and filling out questionnaires. The instruments used are based on indicators of collaborative learning based on the environment project and guidelines for implementing the curriculum of Merdeka made by the Ministry of Education and Culture. The results of this study indicate that there is a significant increase in teachers' perceptions of collaborative learning based on the environment project as a strengthening implementation of the curriculum of Merdeka, which has increased from before and after participating in learning workshops. As many as 84% of teachers have mastered the flow of the project-based collaborative learning model and as many as 74% of teachers have understood the strengthening implementation of the curriculum of Merdeka. This indicates that there has been a significant change in the mastery and understanding of the exact and social teachers in applying the differentiated learning model as a form of strengthening implementation curriculum of Merdeka. In the future, it is necessary to continue training programs or workshops on the strengthening implementation of the curriculum of Merdeka with a focus on other indicators.